SKYSURF. VI. The Impact of Thermal Variations of HST on Background Light Estimates - Isabel A. McIntyre; Timothy Carleton; Rosalia O’Brien; Rogier A. Windhorst; Sarah Caddy; Seth H. Cohen; Rolf A. Jansen; John MacKenty; Scott J. Kenyon (The Astronomical Journal)
The SKYSURF project constrained extragalactic background light and diffuse light (DL) with the vast archive of Hubble Space Telescope (HST) images. Thermal emission from HST itself introduces an additional uncertain background and hinders accurate measurement of the DL level. Here, we use archival Wide Field Camera 3 (WFC3)/IR engineering data to investigate and model changes in the temperature of various components in HSTs optical path as a function of time (solar cycle) and time of the year (Earth–Sun distance). We also specifically investigate changes in temperature with HST's orbital phase and time since Earth occultation. We investigate possible correlations between HST component temperature and year, and temperature and month. The thermal background changes by less than one Kelvin in the WFC3 pickoff mirror, one of the most important contributors to the thermal background. We model these data to describe the impact that orbital phase, year, and time of year have on the HST and WFC3 component temperatures, and use this to derive the impact on the thermal dark signal and the resulting DL measurements. Based on this improved modeling, we provide new upper limits on the level of DL of 21, 32, and 25 nW m ^−2 sr ^−1 for F125W, F140W, and F160W. Additionally, by accounting for all known sources of measurement uncertainty, we report lower limits on the level of DL of 12, 20, and 2 nW m ^−2 sr ^−1 for F125W, F140W, and F160W.